Skip to main content

Some identities for the product of two Bernoulli and Euler polynomials

Abstract

Let n be the space of polynomials of degree less than or equal to n. In this article, using the Bernoulli basis {B0(x), . . . , B n (x)} for n consisting of Bernoulli polynomials, we investigate some new and interesting identities and formulae for the product of two Bernoulli and Euler polynomials like Carlitz did.

1 Introduction

The Bernoulli and Euler polynomials are defined by means of

t e t - 1 e x t = n = 0 B n ( x ) t n n ! , 2 e t + 1 e x t = n = 0 E n ( x ) t n n ! .
(1)

In the special case, x = 0, B n (0) = B n and E n (0) = E n are called the n-th Bernoulli and Euler numbers (see [117]).

From (1), we note that

B n ( x ) = l = 0 n n l B l x n - l , E n ( x ) = l = 0 n n l E l x n - l .
(2)

For n ≥ 0, we have

d d x B n ( x ) = n B n - 1 ( x ) , d d x E n ( x ) = n E n - 1 ( x ) ,
(3)

(see [7, 8]).

By (1), we get the following recurrence for the Bernoulli and the Euler numbers:

B 0 = 1 , B n ( 1 ) - B n = δ 1 , n and E 0 = 1 , E n ( 1 ) + E n = 2 δ 0 , n ,
(4)

where δk, nis the Kronecker symbol (see [117]).

Thus, from (3) and (4), we have

0 1 B n ( x ) d x = δ 0 , n n + 1 , 0 1 E n ( x ) d x = - 2 E n + 1 n + 1 .
(5)

It is known [12] that

0 A B m 1 x a 1 B m n x a n d x = a 1 1 - m 1 a n 1 - m n 0 1 B m 1 ( x ) B m n ( x ) d x ,
(6)

where a1, a2, . . . , a n are positive integers that are relatively prime in pairs A = a1a2 . . . a n .

For n = 2, there is the formula

0 1 B p ( x ) B q ( x ) d x = ( - 1 ) p + 1 B p + q p + q q ,
(7)

where p + q ≥ 2 (see [3, 4]). In [3, 4], we can find the following formula for a product of two Bernoulli polynomials:

B m ( x ) B n ( x ) = r m 2 r n + n 2 r m B 2 r B m + n - 2 r ( x ) m + n - 2 r + ( - 1 ) m + 1 B m + n m + n n , for m + n 2 .
(8)

Assume m, n, p ≥ 1. Then, by (7) and (8), we get

0 1 B m ( x ) B n ( x ) B p ( x ) d x = ( - 1 ) p + 1 p ! r m 2 r n + n 2 r m ( m + n - 2 r - 1 ) ! ( m + n + p - 2 r ) ! B 2 r B m + n + p - 2 r ,
(9)

(see [4]).

In [8], it is known that for n +,

B n ( x ) = k = 0 k 1 n n k B k E n - k ( x )
(10)

and

E n ( x ) = - 2 l = 0 n n l E l + 1 l + 1 B n - l ( x ) .
(11)

Let n = {∑ i a i xi|a i } be the space of polynomials of degree less than or equal to n. In this article, using the Bernoulli basis {B0(x), . . . , B n (x)} for n consisting of Bernoulli polynomials, we investigate some new and interesting identities and formulae for the product of two Bernoulli and Euler polynomials like Carlitz did.

2 Bernoulli identities arising from Bernoulli basis polynomials

From (1), we note that

e x t = 1 t t ( e t - 1 ) e t - 1 e x t = 1 t n = 0 ( B n ( x + 1 ) - B n ( x ) ) t n n ! = 1 t n = 1 ( B n ( x + 1 ) - B n ( x ) ) t n n ! = n = 0 B n + 1 ( x + 1 ) - B n + 1 ( x ) n + 1 t n n ! .
(12)

Thus, from (12), we have

x n = 1 n + 1 ( B n + 1 ( x + 1 ) - B n + 1 ( x ) ) = 1 n + 1 l = 0 n n + 1 l B l ( x ) .
(13)

From (13), we note that {B0(x), B1(x), . . . , B n (x)} spans n . For p(x) n , let p ( x ) = k = 0 n a k B k ( x ) and g(x) = p(x + 1) - p(x). Then we have

g ( x ) = k = 0 n a k ( B k ( x + 1 ) - B k ( x ) ) = k = 0 n k a k x k - 1 .
(14)

From (14), we can derive the following Equation (15):

g ( r ) ( x ) = k = r + 1 n k ( k - 1 ) ( k - r ) a k x k - r - 1 ,
(15)

where g ( r ) ( x ) = d r g ( x ) d x r and r = 0, 1, 2, . . . , n. Let us take x = 0 in (15). Then we have

g ( r ) ( 0 ) = ( r + 1 ) ! a r + 1 .
(16)

By (16), we get, for r = 1, 2, . . . , n,

a r = g ( r - 1 ) ( 0 ) r ! = 1 r ! ( p ( r - 1 ) ( 1 ) - p ( r - 1 ) ( 0 ) ) .
(17)

Let 0=p ( x ) = k = 0 n a k B k ( x ) . Then, from (17), we have

a r = 1 r ! g ( r - 1 ) ( 0 ) = 1 r ! ( p ( r - 1 ) ( 1 ) - p ( r - 1 ) ( 0 ) ) = 0 .
(18)

From (18), we note that {B0(x), B1(x), . . . , B n (x)} is a linearly independent set. Therefore, we obtain the following theorem.

Proposition 1 The set of Bernoulli polynomials {B0(x), B1(x), . . . , B n (x)} is a basis for n .

Let us consider polynomial p(x) n as a linear combination of Bernoulli basis polynomials with

p ( x ) = C 0 B 0 ( x ) + C 1 B 1 ( x ) + + C n B n ( x ) .
(19)

We can write (19) as a dot product of two variables:

p ( x ) = ( B 0 ( x ) , B 1 ( x ) , , B n ( x ) ) C 0 C 1 C n .
(20)

From (20), we can derive the following equation:

p ( x ) = ( 1 , x , x 2 , , x n ) 1 b 12 b 13 b 1 n + 1 0 1 b 23 b 2 n + 1 0 0 1 b 3 n + 1 0 0 0 b n n + 1 0 0 0 1 C 0 C 1 C 2 C n ,
(21)

where b ij are the coefficients of the power basis that are used to determine the respective Bernoulli polynomials. It is easy to show that

B 0 ( x ) = 1 , B 1 ( x ) = x - 1 2 , B 2 ( x ) = x 2 - x + 1 6 , B 3 ( x ) = x 3 - 3 2 x 2 + 1 2 x , .

In the quadratic case (n = 2), the matrix representation is

p ( x ) = ( 1 , x , x 2 ) 1 - 1 2 1 6 0 1 - 1 0 0 1 C 0 C 1 C 2 .
(22)

In the cubic case (n = 3), the matrix representation is

p ( x ) = ( 1 , x , x 2 , x 3 ) 1 - 1 2 1 6 0 0 1 - 1 1 2 0 0 1 - 3 2 0 0 0 1 C 0 C 1 C 2 C 3 .
(23)

In many applications of Bernoulli polynomials, a matrix formulation for the Bernoulli polynomials seems to be useful.

There are many ways of obtaining polynomial identities in general. Here, in Theorems 2-9, we use the Bernoulli basis in order to express certain polynomials as linear combinations of that basis and hence to get some new and interesting polynomial identities.

Let I m , n = 0 1 B m ( x ) B n ( x ) dx for m,n + . Then, by integration by parts, we get

I 0 , n = I m , 0 = 0 , I m , n = ( - 1 ) m + n B m + n m + n m , ( m , n 2 ) .
(24)

For n + with n ≥ 2, let us consider the following polynomials in n :

p ( x ) = k = 0 n B k ( x ) B n - k ( x ) n .
(25)

Then, from (25), we have

p ( r ) ( x ) = ( n + 1 ) ! ( n - r + 1 ) ! k = r n B k - r ( x ) B n - k ( x ) ,
(26)

where r = 0, 1, 2, . . . n.

By Proposition 1, we see that p(x) can be written as

p ( x ) = k = 0 n a k B k ( x ) .
(27)

From (25) and (27), we note that

a 0 = 0 1 p ( t ) d t = k = 0 n I k , n - k = B n k = 1 n - 1 ( - 1 ) k - 1 n k = B n ( 1 + ( - 1 ) n ) n + 2 = 2 n + 2 B n .

By (18) and (26), we get

a r + 1 = 1 ( r + 1 ) ! ( p ( r ) ( 1 ) - p ( r ) ( 0 ) ) = ( n + 1 ) ! ( r + 1 ) ! ( n - r + 1 ) ! k = r n ( B k - r ( 1 ) B n - k ( 1 ) - B k - r B n - k ) = 1 n + 2 n + r r + 1 k = r n { ( δ 1 , k - r + B k - r ) ( δ 1 , n - k + B n - k ) - B k - r B n - k } = 1 n + 2 n + 2 r + 1 ( B n - r - 1 + B n - r - 1 + δ r , n - 2 ) = 2 n + 2 n + 2 r + 1 B n - r - 1 if  r n - 2 . 0 if  r = n - 2 .
(28)

Therefore, by (25), (27) and (28), we obtain the following theorem.

Theorem 2 For n + with n ≥ 2, we have

k = 0 n B k ( x ) B n - k ( x ) = 2 n + 2 k = 0 n - 2 n + 2 k B n - k B k ( x ) + ( n + 1 ) B n ( x ) .

For n + with n ≥ 2, let us take polynomial p(x) in n as follows:

p ( x ) = k = 0 n 1 k ! ( n - k ) ! B k ( x ) B n - k ( x ) n .
(29)

From Proposition 1, we note that p(x) is given by means of Bernoulli basis polynomials:

p ( x ) = k = 0 n a k B k ( x ) n .
(30)

By (24), (29) and (30), we get

a 0 = 0 1 p ( t ) d t = k = 0 n 1 k ! ( n - k ) ! I k , n - k = 2 I 0 , n n ! + k = 1 n - 1 ( - 1 ) k - 1 k ! ( n - k ) ! n k B n = B n n ! k = 1 n - 1 ( - 1 ) k - 1 = B n n ! ( 1 + ( - 1 ) n ) 2 = B n n ! .
(31)

From (29), we have that for r = 0, 1, 2, . . . , n,

p ( r ) ( x ) = 2 r k = r n B k - r ( x ) B n - k ( x ) ( k - r ) ! ( n - k ) ! .
(32)

By (18), we get

a r + 1 = 1 ( r + 1 ) ! ( p ( r ) ( 1 ) - p ( r ) ( 0 ) ) = 2 r ( r + 1 ) ! k = r n 1 ( k - r ) ! ( n - k ) ! ( B k - r ( 1 ) B n - k ( 1 ) - B k - r B n - k ) = 2 r ( r + 1 ) ! 2 B n - r - 1 ( n - 1 - r ) ! + k = r n δ 1 , k - r δ 1 , n - k = 2 r + 1 n ! n r + 1 B n - r - 1 if  r n - 2 , 0 if  r = n - 2 .
(33)

Therefore, from (29), (30) and (33), we obtain the following theorem.

Theorem 3 For n + with n ≥ 2, we have

k = 0 n n k B k ( x ) B n - k ( x ) = k = 0 k n - 1 n 2 k n k B n - k B k ( x ) .

Let n + with n ≥ 2. Then we consider polynomial p(x) in n with

p ( x ) = k = 1 n - 1 1 k ( n - k ) B k ( x ) B n - k ( x ) .

By Proposition 1, we see that p(x) is written as

p ( x ) = k = 0 n a k B k ( x ) .
(34)

From (34), we have

a 0 = 0 1 p ( t ) d t = k = 1 n - 1 1 k ( n - k ) 0 1 B k ( t ) B n - k ( t ) d t = k = 1 n - 1 1 k ( n - k ) ( - 1 ) k - 1 n k B n = 1 + ( - 1 ) n n 2 B n = 2 B n n 2 .

It is easy to show that for r = 1, 2 , . . . , n - 1,

p ( r ) ( x ) = 2 C r B n - r ( x ) + ( n - 1 ) ( n - r ) k = r + 1 n - 1 B k - r ( x ) B n - k ( x ) ( k - r ) ( n - k ) ,
(35)

where C r = 1 n - r j = 1 r ( n - 1 ) ... ( n - j + 1 ) ( n - j - 1 ) ... ( n - r ) .

By (17), we get

a r + 1 = 1 ( r + 1 ) ! ( p ( r ) ( 1 ) - p ( r ) ( 0 ) ) = 1 ( r + 1 ) ! 2 C r ( B n - r ( 1 ) - B n - r ) + ( n - 1 ) ( n - r ) k = r + 1 n - 1 B k - r ( 1 ) B n - k ( 1 ) - B k - r B n - k ( k - r ) ( n - k ) = 2 C r ( r + 1 ) ! δ r , n - 1 + 1 n n r + 1 k = r + 1 n - 1 B k - r δ 1 , n - k + δ 1 , k - r B n - k + δ 1 , k - r δ 1 , n - k ( k - r ) ( n - k ) = 2 n ( n - r - 1 ) n r + 1 B n - r - 1 if 0 r n - 3 , 0 if r = n - 2 , 2 n ! C n - 1 if r = n - 1 .
(36)

From the definition of C r , we have

2 n ! C n - 1 = 2 n ! i = 1 n - 1 ( n - 1 ) ! n - i = 2 n i = 1 n - 1 1 i = 2 n H n - 1 ,
(37)

where H n = i = 1 n 1 i .

Therefore, by (34), (36) and (37), we obtain the following theorem.

Theorem 4 For n + with n ≥ 2, we have

k = 1 n - 1 B k ( x ) B n - k ( x ) k ( n - k ) = 2 n k = 0 n - 2 1 n - k n k B n - k B k ( x ) + 2 n H n - 1 B n ( x ) .

Let J m , n = 0 1 E m ( t ) E n ( t ) dt, for m, n +. Then we see that

J m , n = 2 ( - 1 ) m - 1 ( n + m + 1 ) n + m m E n + m + 1 , ( see [ 3 , 4 , 7 , 8 ] ) .
(38)

Let us take polynomials p(x) in n with p ( x ) = k = 0 n E k ( x ) E n - k ( x ) . Then, by Proposition 1, p(x) is written as p ( x ) = k = 0 n a k B k ( x ) .

It is not difficult to show that

a 0 = 0 1 p ( t ) d t = k = 0 n J k , n - k = 2 E n + 1 n + 1 k = 0 n ( - 1 ) k - 1 n k = - 2 E n + 1 1 + ( - 1 ) n n + 2 = - 4 E n + 1 n + 2

and

p ( r ) ( x ) = ( n + 1 ) ! ( n + 1 - r ) ! k = r n E k - r ( x ) E n - k ( x ) , ( r = 0 , 1 , 2 , , n ) .
(39)

By (17) and (39), we get

a k = 1 k ! ( p ( k - 1 ) ( 1 ) - p ( k - 1 ) ( 0 ) ) = ( n + 1 ) ! k ! ( n - k + 2 ) ! l = k - 1 n ( E l - k + 1 ( 1 ) E n - l ( 1 ) - E l - k + 1 E n - l ) = n + 2 k n + 2 l = k - 1 n { ( - E l - k + 1 + 2 δ 0 , l - k + 1 ) ( - E n - l + 2 δ 0 , n - l ) - E l - k + 1 E n - l } = - 4 n + 2 k n + 2 E n - k + 1 ,
(40)

where k = 0, 1, 2, . . . , n. Therefore, by (40), we obtain the following theorem.

Theorem 5 For n +, we have

k = 0 n E k ( x ) E n - k ( x ) = - 4 n + 2 k = 0 n n + 2 k E n - k + 1 B k ( x ) .

Let us take the polynomial p(x) in n as follows:

p ( x ) = k = 0 n 1 k ! ( n - k ) ! E k ( x ) E n - k ( x ) .
(41)

Then, by (41), we get

p ( r ) ( x ) = 2 r k = r n E k - r ( x ) E n - k ( x ) ( k - r ) ! ( n - k ) ! ,
(42)

where r = 0, 1, 2, . . . , n.

By Proposition 1, we see that p(x) can be written as

p ( x ) = k = 0 n a k B k ( x ) .
(43)

From (41), (42) and (43), we have

a 0 = 0 1 p ( t ) d t = k = 0 n 1 k ! ( n - k ) ! J k , n - k = 2 E n + 1 ( n + 1 ) ! k = 0 n ( - 1 ) k - 1 = - 2 E n + 1 ( n + 1 ) ! 1 + ( - 1 ) n 2 = - 2 E n + 1 ( n + 1 ) !
(44)

and

a r = 1 r ! ( p ( r - 1 ) ( 1 ) - p ( r - 1 ) ( 0 ) ) = 2 r - 1 r ! k = r - 1 n E k - r + 1 ( 1 ) E n - k ( 1 ) - E k - r + 1 E n - k ( k - r + 1 ) ! ( n - k ) ! = 2 r - 1 r ! - 2 E n - r + 1 ( n - r + 1 ) ! - 2 E n - r + 1 ( n - r + 1 ) ! + 4 δ n + 1 , r = - 2 r + 1 ( n + 1 ) ! n + 1 r E n - r + 1 ,
(45)

where r = 1, 2, . . . , n.

Therefore, by (41), (43) and (45), we obtain the following theorem.

Theorem 6 For n +, we have

k = 0 n n k E k ( x ) E n - k ( x ) = - 2 n + 1 k = 0 n 2 k n + 1 k E n - k + 1 B k ( x ) .

Let us take

p ( x ) = k = 1 n - 1 1 k ( n - k ) E k ( x ) E n - k ( x )

in n . Then, by Proposition 1, p(x) is given by means of basis polynomials:

p ( x ) = k = 0 n a k B k ( x ) .
(46)

It is easy to show that

a 0 = 0 1 p ( t ) d t = k = 1 n - 1 1 k ( n - k ) J k , n - k = 2 E n + 1 n + 1 k = 1 n - 1 1 k ( n - k ) ( - 1 ) k - 1 n k = 2 ( 1 + ( - 1 ) n ) n 2 ( n + 1 ) E n + 1 = 4 E n + 1 n 2 ( n + 1 )

and

p ( k ) ( x ) = 2 C k E n - k ( x ) + ( n - 1 ) ( n - k ) l = k + 1 n - 1 E l - k ( x ) E n - l ( x ) ( l - k ) ( n - l ) , ( k = 1 , 2 , , n - 1 )

where C k = 1 ( n - k ) j = 1 k ( n - 1 ) ( n - j + 1 ) ( n - j - 1 ) ( n - k ) .

By the same method, we get

a k = 1 k ! ( p ( k - 1 ) ( 1 ) - p ( k - 1 ) ( 0 ) ) = 1 k ! 2 C k - 1 ( E n - k + 1 ( 1 ) - E n - k + 1 ) + ( n - 1 ) ( n - k + 1 ) l = k n - 1 E l - k + 1 ( 1 ) E n - l ( 1 ) - E l - k + 1 E n - l ( l - k + 1 ) ( n - l ) = - 4 C k - 1 k ! E n - k + 1 .

From the construction of C k , we note that

C k - 1 k ! = 1 k ! ( n - k + 1 ) j = 1 k - 1 ( n - 1 ) ( n - j + 1 ) ( n - j - 1 ) ( n - k + 1 ) = 1 k ! ( n - k + 1 ) j = 1 k - 1 ( n - 1 ) ! ( n - k ) ! ( n - j ) = n k n ( n - k + 1 ) j = 1 k - 1 1 n - j = n k n ( n - k + 1 ) j = 1 n - 1 1 j - j = 1 n - k 1 j = n k n ( n - k + 1 ) ( H n - 1 - H n - k ) .

Therefore, by the same method, we obtain the following theorem.

Theorem 7 For n + with n ≥ 2, we have

k = 1 n - 1 E k ( x ) E n - k ( x ) k ( n - k ) = 4 E n + 1 n 2 ( n + 1 ) - 4 n k = 1 n n k n - k + 1 ( H n - 1 - H n - k ) E n - k + 1 B k ( x ) .

Let

T m , n = 0 1 B m ( t ) E n ( t ) d t , for m , n + .
(47)

From (47), we have that

T m , 0 = 0 1 B m ( t ) d t = δ 0 , m m + 1 and T 0 , n = 0 1 E n ( t ) d t = - 2 E n + 1 n + 1 .

For m, n , we have

T m , n = 2 ( - 1 ) m ( m + n + 1 ) m + n m l = m + 1 m + n ( - 1 ) l m + n + 1 l B l E n + m + 1 - l .
(48)

Let us consider the following polynomial in n :

p ( x ) = k = 0 n B k ( x ) E n - k ( x ) .
(49)

For n with n ≥ 2, by Proposition 1, p(x) is given by

p ( x ) = k = 0 n a k B k ( x ) .
(50)

From (49) and (50), we note that

a 0 = 0 1 p ( t ) d t = T 0 , n + k = 1 n - 1 T k , n - k + T n , 0 = - 2 E n + 1 n + 1 + 2 n + 1 k = 1 n - 1 l = k + 1 n ( - 1 ) k + l n + 1 l n k B l E n + 1 - l .
(51)

For k = 0, 1, 2, . . . , n, we have

p ( k ) ( x ) = ( n + 1 ) n ( n + 2 - k ) l = k n B l - k ( x ) E n - l ( x ) = ( n + 1 ) ! ( n - k + 1 ) ! l = k n B l - k ( x ) E n - l ( x ) .
(52)

By (17), we get

a k = 1 k ! ( p ( k - 1 ) ( 1 ) - p ( k - 1 ) ( 0 ) ) = ( n + 1 ) ! k ! ( n - k + 2 ) ! l = k - 1 n ( B l - k + 1 ( 1 ) E n - l ( 1 ) - B l - k + 1 E n - l ) = n + 2 k n + 2 l = k - 1 n { ( B l - k + 1 + δ 1 , l - k + 1 ) ( - E n - l + 2 δ 0 , n - l ) - B l - k + 1 E n - l } = n + 2 k n + 2 - 2 l = k - 1 n B l - k + 1 E n - l - E n - k + 2 B n - k + 1 + 2 δ n , k .
(53)

Therefore, by (49), (50) and (53), we obtain the following theorem.

Theorem 8 For n + with n ≥ 2, we have

k = 0 n B k ( x ) E n - k ( x ) = - 2 E n + 1 n + 1 + 2 n + 1 k = 1 n - 1 l = k + 1 n ( - 1 ) k + l n + 1 l n k B l E n + 1 - l + ( n + 1 ) B n ( x ) + 1 n + 2 k = 1 n - 2 n + 2 k - 2 l = k - 1 n B l - k + 1 E n - l - E n - k + 2 B n - k + 1 B k ( x ) .

For n with n ≥ 2, let us take p ( x ) = k = 0 n B k ( x ) E n - k ( x ) k ! ( n - k ) ! in n . Then we have

p ( k ) ( x ) = 2 k l = k n 1 ( l - k ) ! ( n - l ) ! B l - k ( x ) E n - l ( x ) .
(54)

From Proposition 1, we note that p(x) can be written as

p ( x ) = k = 0 n a k B k ( x ) .
(55)

Thus, by (55), we get

a 0 = 0 1 p ( t ) d t = k = 0 n 1 k ! ( n - k ) ! T k , n - k = T 0 , n n ! + k = 1 n - 1 T k , n - k k ! ( n - k ) ! + T n , 0 n ! = - 2 E n + 1 ( n + 1 ) ! + 2 ( n + 1 ) ! k = 1 n - 1 l = k + 1 n ( - 1 ) k + l n + 1 l B l E n + 1 - l .
(56)

From (17), we note that

a k = 1 k ! ( p ( k - 1 ) ( 1 ) - p ( k - 1 ) ( 0 ) ) = 2 k - 1 k ! l = k - 1 n B l - k + 1 ( 1 ) E n - l ( 1 ) - B l - k + 1 E n - l ( l - k + 1 ) ! ( n - l ) ! = 2 k - 1 k ! l = k - 1 n - 2 B l - k + 1 E n - l ( l - k + 1 ) ! ( n - l ) ! - E n - k ( n - k ) ! + 2 B n - k + 1 ( n - k + 1 ) ! + 2 δ n , k .
(57)

Therefore, by (54), (55) and (57), we obtain the following theorem.

Theorem 9 For n with n ≥ 2, we have

k = 0 n n k B k ( x ) E n - k ( x ) = - 2 E n + 1 n + 1 + 2 n + 1 k = 1 n - 1 l = k + 1 n ( - 1 ) k + l n + 1 l B l E n + 1 - l + k = 1 n - 2 - 2 k n + 1 k n + 1 l = k - 1 n n - k + 1 n - l B l - k + 1 E n - l - 2 k - 1 n k E n - k + 2 k n + 1 k n + 1 B n - k + 1 B k ( x ) + 2 n B n ( x ) .

For n with n ≥ 2, let us consider the polynomial p ( x ) = k = 1 n - 1 B k ( x ) E n - k ( x ) k ( n - k ) in n .

From Proposition 1, we note that p(x) can be written as p ( x ) = k = 0 n a k B k ( x ) . Then the k-th derivative of p(x) is given by

p ( k ) ( x ) = C k ( B n - k ( x ) + E n - k ( x ) ) + ( n - 1 ) ( n - k ) l = k + 1 n B l - k ( x ) E n - l ( x ) ( l - k ) ( n - l ) ,
(58)

where k = 1, 2, . . . , n - 1 and

C k = 1 n - k j = 1 k ( n - 1 ) ( n - 2 ) ( n - j + 1 ) ( n - j - 1 ) ( n - k ) .

In addition,

p ( n ) ( x ) = ( p ( n - 1 ) ( x ) ) = C n - 1 ( B 1 ( x ) + E 1 ( x ) ) = 2 C n - 1 = 2 ( n - 1 ) ! H n - 1 .

From (17), we note that

a k = 1 k ! ( p ( k - 1 ) ( 1 ) - p ( k - 1 ) ( 0 ) ) = C k - 1 k ! { ( B n - k + 1 ( 1 ) - B n - k + 1 ) + ( E n - k + 1 ( 1 ) - E n - k + 1 ) } + ( n - 1 ) ( n - k + 1 ) k ! l = k n - 1 1 ( l - k + 1 ) ( n - l ) ( B l - k + 1 ( 1 ) E n - l ( 1 ) - B l - k + 1 E n - l ) = C k - 1 k ! ( - 2 E n - k + 1 + δ 1 , n - k + 1 ) + n k n l = k n - 1 - 2 B l - k + 1 E n - l ( l - k + 1 ) ( n - l ) - E n - k n - k .
(59)

It is easy to show that

a 0 = 0 1 p ( t ) d t = k = 1 n - 1 1 k ( n - k ) T k , n - k = 2 ( n + 1 ) n ( n - 1 ) k = 0 n - 2 ( - 1 ) k + 1 n - 2 k l = k + 2 n ( - 1 ) l n + 1 l B l E n + 1 - l .
(60)

Therefore, from (59) and (60), we have

k = 1 n - 1 1 k ( n - k ) B k ( x ) E n - k ( x ) = 2 n ( n 2 - 1 ) k = 0 n - 2 l = k + 2 n ( - 1 ) k + l + 1 n + 1 l n - 2 k B l E n + 1 - l + k = 1 n - 2 - 2 n ( n - k + 1 ) n k ( H n - 1 - H n - k ) E n - k + 1 + 1 n n k - 2 l = k n - 1 B l - k + 1 E n - l ( l - k + 1 ) ( n - l ) - E n - k n - k B k ( x ) + 2 n H n - 1 B n ( x ) .

References

  1. 1.

    Araci S, Erdal D, Seo JJ: A study on the fermionic p -adics q -integral representation on p associated with weighted q -Bernstein and q -Genocchi polynomials. Abstr Appl Anal 2011, 2011: 10. (Article ID 649248)

    MathSciNet  Article  MATH  Google Scholar 

  2. 2.

    Bayad A: Modular properties of elliptic Bernoulli and Euler functions. Adv Stud Contemp Math 2010, 20(3):389–401.

    MathSciNet  MATH  Google Scholar 

  3. 3.

    Carlitz L: Product of two Eulerian polynomials. Math Mag 1963, 36: 37–41. 10.2307/2688134

    MathSciNet  Article  MATH  Google Scholar 

  4. 4.

    Carlitz L: Note on the integral of the product of several Bernoulli polynomials. J Lond Math Soc 1959, 34: 361–363. 10.1112/jlms/s1-34.3.361

    Article  MathSciNet  MATH  Google Scholar 

  5. 5.

    Cangul IN, Kurt V, Ozden H, Simsek Y: On the higher-order w - q -Genocchi numbers. Adv Stud Contemp Math 2009, 19: 39–57.

    MathSciNet  MATH  Google Scholar 

  6. 6.

    Cenkci M, Simsek Y, Kurt V: Multiple two-variable p -adic q - L -function and its be-havior at s = 0. Russ J Math Phys 2008, 15: 447–459. 10.1134/S106192080804002X

    MathSciNet  Article  MATH  Google Scholar 

  7. 7.

    Kim DS, Kim T: A study on the integral of the product of several Bernoulli polynomials. Rocky Mountain Journal of Mathematics, in press.

  8. 8.

    Kim DS, Dolgy DV, Kim HM, Lee SH, Kim T: Integral formula of Bernoulli polynomials. Adv Stud Contemp Math 2012, 22(2):190–199.

    MathSciNet  MATH  Google Scholar 

  9. 9.

    Kim T: An identity of symmetry for the generalized Euler polynomials. J Comput Anal Appl 2011, 13(7):1292–1296.

    MathSciNet  MATH  Google Scholar 

  10. 10.

    Kim T: Some identities for the Bernoulli, the Euler and the Genocchi numbers and polynomials. Adv Stud Contemp Math 2010, 20: 23–28.

    MathSciNet  MATH  Google Scholar 

  11. 11.

    Kim T: q -Bernoulli numbers and polynomials associated with Gaussian binomial coefficients. Russ J Math Phys 2008, 15: 51–57.

    MathSciNet  Article  MATH  Google Scholar 

  12. 12.

    Mordell LJ: Integral formulas of arithmetic characters. J Lond Math Soc 1957, 33: 371–375.

    MathSciNet  Google Scholar 

  13. 13.

    Ozden H, Simsek Y: A new extension of q -Euler numbers and polynomials related to their interpolation functions. Appl Math Lett 2008, 21(9):934–939. 10.1016/j.aml.2007.10.005

    MathSciNet  Article  MATH  Google Scholar 

  14. 14.

    Ryoo CS: Some relations between twisted q -Euler numbers and Bernstein polynomials. Adv Stud Contemp Math 2011, 21(2):217–223.

    MathSciNet  MATH  Google Scholar 

  15. 15.

    Ryoo CS: Some identities of the twisted q -Euler numbers and polynomials associated with q -Bernstein polynomials. Proc Jangjeon Math Soc 2011, 14(2):239–248.

    MathSciNet  MATH  Google Scholar 

  16. 16.

    Simsek Y: Complete sum of products of ( h , q )-extension of Euler polynomials and numbers. J Diff Equ Appl 2010, 16(11):1331–1348. 10.1080/10236190902813967

    MathSciNet  Article  MATH  Google Scholar 

  17. 17.

    Simsek Y: Theorems on twisted L -function and twisted Bernoulli numbers. Adv Stud Contemp Math 2005, 11(2):205–218.

    MathSciNet  MATH  Google Scholar 

Download references

Acknowledgements

The authors would like to express their deep gratitudes to the referees for their valuable suggestions and comments.

Author information

Affiliations

Authors

Corresponding author

Correspondence to Taekyun Kim.

Additional information

Competing interests

The authors declare that they have no competing interests.

Authors' contributions

All authors contributed equally to the manuscript and typed, read and approved the final manuscript.

Rights and permissions

Open Access This article is distributed under the terms of the Creative Commons Attribution 2.0 International License (https://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Reprints and Permissions

About this article

Cite this article

Kim, D.S., Kim, T., Lee, SH. et al. Some identities for the product of two Bernoulli and Euler polynomials. Adv Differ Equ 2012, 95 (2012). https://doi.org/10.1186/1687-1847-2012-95

Download citation

Keywords

  • Differential Equation
  • Positive Integer
  • Linear Combination
  • Partial Differential Equation
  • Ordinary Differential Equation